2008
DOI: 10.1016/j.avsg.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Calcification Increases in Distal Arteries in Patients with Peripheral Arterial Disease

Abstract: Objective-The aim of this study was to determine if significant differences in plaque composition exist between the popliteal and tibial vessels in patients with severe peripheral arterial disease (PAD).Methods-Forty-four patients with PAD required either above knee (n=38), below knee (n=5) or through knee (n=1) amputation for pedal sepsis/gangrene. The fifty-one vessels (anterior tibial, n=9; posterior tibial, n=10; peroneal, n=3; popliteal, n=29) were obtained, and underwent intravascular ultrasound (IVUS) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Additionally, the significant difference in TBR between the peripheral and carotid arteries seen in this study as well as in previous studies (6,7,13) suggests that the degree of inflammation in symptomatic peripheral atherosclerosis is lower than in carotid atherosclerosis. This finding may be due to differences in their pathogenesis: femoral lesions are more likely to be composed of fibrous and calcified material, which accumulates less FDG than lipid-rich, inflamed plaque (17,18). Calcification in the peripheral and carotid arteries was in fact a common finding on the CT images in this study, and previous studies do reveal that inflammation and calcification rarely coexist in the same plaque (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the significant difference in TBR between the peripheral and carotid arteries seen in this study as well as in previous studies (6,7,13) suggests that the degree of inflammation in symptomatic peripheral atherosclerosis is lower than in carotid atherosclerosis. This finding may be due to differences in their pathogenesis: femoral lesions are more likely to be composed of fibrous and calcified material, which accumulates less FDG than lipid-rich, inflamed plaque (17,18). Calcification in the peripheral and carotid arteries was in fact a common finding on the CT images in this study, and previous studies do reveal that inflammation and calcification rarely coexist in the same plaque (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, atherectomy devices as well as stenting are indicated (class IIb) as “salvage” devices to be used in the event of suboptimal BA results 3. The presence of calcified plaque in femoropopliteal lesions is common, and arterial wall calcium is associated with higher rates of procedural complications, including flow-limiting dissections which frequently require stent deployment to maintain vessel patency 5,6. Further, stenting as salvage therapy in calcified segments after failed BA often results in stent underexpansion and malapposition, which increase the probability of subsequent stent fracture and/or restenosis 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…20 Compared to PAD patients with popliteal disease, VH-IVUS showed that patients with tibial disease had less fibrous and fibrofatty plaque, more calcified plaque, and similar LCP. 21 The present study is the first to use NIRS-IVUS to characterize the composition of atherosclerotic plaque in patients with symptomatic PAD. Although the observed prevalence of fibrocalcific plaque (97.8%) is much higher than prior autopsy and MRI studies, the differences are probably due to the presence of severe PAD in all of our patients.…”
Section: Currently Available Intravascular Imaging Techniques Includementioning
confidence: 99%